The effects of translanguaging treatment on reading literacy performance in Grade 3 and 4 classrooms - Thusi, Thandeka (My University, 2020)
The multilingual landscape of South African schools has been viewed as a barrier for literacy development where English-only language in education practices continue to dominate. While the South African education system has adopted a language in education policy (1997), which is in support of multilingual education, the development of multilingual pedagogies and their impact on literacy development has not been adequately explored. Against this background, this study investigated the effectiveness of using translanguaging as a multilingual strategy for reading literacy trajectories in Grades 3 and 4 classes. The study is contextualised within scholarly literature that deals with themes that include automaticity, simple view of reading, translanguaging, early grade reading and oral classroom interactions which have been researched globally. Review of the literature under these research themes revealed that there was no adequate attention on reading literacy development between phases in multilingual contexts, which provide the rationale for the current study to fill in the gap. Through a mixed method approach, the study first adopted a translingual lens to observe literacy events that occur in the classrooms. Secondly, the study engaged with metacognitive reflections of teachers’ account of own lessons where teaching occurred in more than one language. Lastly, through analysis of a battery of literacy tests written by grade 3 and 4 learners, the study established the learners’ reading and comprehension skills in isiZulu and English. The results of the learners’ assessments were compared to determine the transition from foundation phase (Grades 1-3) to the intermediate phase (Grades 4-6) and ascertain whether or not there were patterns of a Grade 4 slump. The findings of the study indicate the level of engagement by the learners in literacy events was not high and a low teacher impact was observed. Secondly, the study found that while teachers were aware of their learners having reading difficulties, their expectations of the learners were higher than the results produced by their learners in the multilingual assessments that were administered. Noteworthy was their acknowledgement that their learners’ reading development in their home language was lower than their competencies in English. Lastly, the study found that the learners’ literacy development was significantly lower than the international benchmark and that the transition from Grade 3 to 4 did not result in an improved result for the literacy development in both English and isiZulu. Given these findings, the learners’ engagement in literacy events must increase to improve literacy skills of learners. In addition, there needs to be an improvement in the reading development of learners’ home language so as to upscale the literacy development of the learners. Given the limitations in the scope of the study, further research on the efficacy of translanguaging on a large scale is urgently needed to augment the findings of the study.
A thesis submitted in fulfilment of the requirements for the degree of Master of Education to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand Johannesburg, 2020
Keywords: Translanguaging (Linguistics); Semiotics--Social aspects